The Relationship between Employees Training and Job Satisfaction with Moderating Role of Organizational Culture. A Case of Banking Sector of KP, Pakistan - Aziz Ullah (Journal of Accounting and Finance in Emerging Economies, 2020)
Employee job satisfaction has been widely acknowledged as one of the most important factors in the performance and productivity of the employees working in an organization. There are certain factors that contribute towards the job satisfaction of the employee’s and one such widely renowned factor is the training of the employees. The relationship between job satisfaction and the training of employees is further moderated by the organizational culture. This study analyzed the impacts of employees training on the level of their job satisfaction under the moderating effects of the organizational culture. Three different dimensions of satisfaction i.e. satisfaction with Pay, work itself and interpersonal relationship was analyzed in the study. Primary data was collected from as ample of 200 employees from different banks operating in Khyber Pakhtunkhwa, Pakistan. The data was analyzed using descriptive statistics, T-test and regression analysis techniques. The results of the study presented that Hierarchy and Adhocracy culture are the two most dominant cultures prevailing in the banking sector of Pakistan. The results further present that training has significant association with the level of job satisfaction of the employees with their, pay, work itself and interpersonal relationship. The results further established the moderating role of Adhocracy and Hierarchy Culture in determining the relationship between Training and job satisfaction of the employees.